Coding Without Computers: Sixth-Grade Students' Responses to Unplugged Coding-Based Science Worksheets in Elementary Schools - Nurhayati Nurhayati; Hisny Fajrussalam; Nenden Permas Hikmatunisa; Mariano Dos Santos (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Computational thinking is an increasingly essential 21st-century skill that helps students think and solve problems logically, and its integration into science education is growing in importance. Many elementary schools, however, face limited digital infrastructure that constrains computational thinking implementation, making unplugged coding, programming instruction without digital devices, a practical alternative for developing this skill. Previous studies on unplugged coding have mostly examined its cognitive and skill-based outcomes, while research on students' affective responses to unplugged coding-based materials in science learning remains limited. This study aimed to analyse sixth-grade students' responses to a science student worksheet based on unplugged coding, focusing on four indicators: format, relevance, confidence, and interest. The study employed a quantitative descriptive design involving 98 sixth-grade students from an elementary school in Purwakarta Regency, selected through purposive sampling. Data were collected using a validated four point likert-scale questionnaire adapted from the ARCS (attention, relevance, confidence, satisfaction) motivation model and analysed descriptively to determine mean values, percentages, and standard deviations. The findings showed that students responded very positively to the worksheet, with an overall average score of 88.79%, categorised as excellent. The format indicator recorded the highest score (90.56%), followed by confidence (88.62%), interest (88.01%), and relevance (87.96%), indicating that students found the worksheet engaging and supportive of their confidence and understanding of science material. These results suggest that unplugged coding-based worksheets can transform abstract concepts into concrete, interactive, and enjoyable learning activities, offering a practical solution for science instruction in schools with limited technological resources